Challenges of the Pandemic Response in Primary Care during Pre-Vaccination Period: A Qualitative Study. Issue 1 (December 2015) - Kunin, Marina; Engelhard, Dan; Thomas, Shane; Ashworth, Mark; Piterman, Leon
Abstract Background During the 2009/A/H1N1 pandemic, the main burden of the patient management fell on primary care physicians (PCPs), and they were the principal implementers of pandemic policies. Broad involvement of PCPs in the pandemic response offered an excellent opportunity to investigate the challenges that they encountered. Objective To examine challenges faced by PCPs as they implemented pandemic policies in Australia, Israel and England before the 2009/A/H1N1 pandemic vaccine became available. Methods This is a qualitative descriptive study that employed in-depth semi-structured interviews with 65 PCPs from Australia, Israel and England. The data were analysed thematically to provide a detailed account of the themes. Results Challenges in three fields of the pandemic response were identified. (i) Consultation of patients was challenged by the high flow of patients, sick and worried-well, the necessity to provide personalised information about the disease during consultations, and unfamiliar antiviral treatment. (ii) Performance of public health responsibilities was complicated in regards to patient segregation and introduction of personal protection measures. (iii) Communication with the health authorities was inefficient, with no established route to provide feedback about the pandemic policies. Conclusions The experience of the 2009/A/H1N1 pandemic highlighted the centrality of primary care in the pandemic response. Despite intensive pre-pandemic planning, numerous barriers for implementation of the pandemic policies in primary care were identified. Investigation of three different approaches for involvement of PCPs in the pandemic management showed that none of these approaches worked smoothly.